(untitled) - Weinstein, Franklin B. (Boulder, Colo., 1978)
The book presented about foreign relations of Japan with U.S and foreign relations United States with East Asia.
Keywords: United states,Japan,East asia; Foreign relations,Foreign relations,Foreign relations; Japan,United states,United states